PRESTASI BELAJAR ILMU PENGETAHUAN SOSIAL SISWA SEKOLAH MENENGAH PERTAMA DITINJAU DARI MINAT DAN MOTIVASI - Purwanto Yugo Yuwono (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
Abstract: This study aims to analyze and test the truth of the hypothesis regarding the effect of student interest and motivation on learning achievement. From the hypothesis testing, the results show that: (1) There is a significant influence on student interest and motivation to study together on learning achievement., (2) There is a significant influence on student interest in learning achievement, (3) There is a significant influence on motivation student learning on learning achievement.Keywords: Interests, Motivation, Learning Achievement